Building inclusive learning environment through hybrid learning system: Role of technology and corresponding engagement - Yasser Arfat; Muhammad Khalid Shahid; Raed Saud Al-tayyar; Khalid Mahmood; Ahmed Alghamdi (Sustainable Futures, 2025)
The effective management with online resources has always been influential in hybrid learning systems, particularly in fostering inclusive learning environment. In this connection, this study examines the impact of technological infrastructure and preparedness to examine their effects on the perceived effectiveness of a hybrid learning system applying the Community of Inquiry (CoI) framework from quantitative aspects. Data were collected from university students in Pakistan using a questionnaire and analysed using a covariance-based structural equation model (CB-SEM). The results revealed that technological infrastructure has a significant positive relationship with conscious attention and affection while a positive but insignificant relationship with enthused participation and social connectedness. The relationship of preparedness with conscious attention, enthused participation, affection, and social connectedness was found significant and positive. The impact of conscious attention, enthused participation, and affection on perceived learning effectiveness was found to be positive and significant however, it was not significant in the case of social connectedness . The finding underscores the need for sufficient investment in technological infrastructure to create inclusive, resilient and high-quality learning environment. This way, the study contributes to the existing body of knowledge through examination of critical role of engagement with online resources in achieving impartial and quality hybrid learning system.